Recent Minimalist Developments and the Nothion of Subjecthood - Miechowicz-Mathiasen, Katarzyna (My University, 2006)
The goal of this paper is to define the notion of subjecthood in syntactic terms. We base our assumptions on Ura’s (2000) feature checking theory and his idea of defining Grammatical Relations on that basis. We reanalyse his ideas in terms of Chomskyan (2001) most recent Probe/Goal system. Following Ura (2000), we assume that such standard subject properties as binding a reflexive, controlling a missing subject in a subordinate clause and raising, result from a feature checking relation established with the T head/Probe while checking off the following features of T in the course of the derivation: [EPP], [Φ] and/or [CASE]. We present an analysis of both Nominative and Non-Nominative Subject Constructions in Polish and English (Old and Middle English) and propose parameter settings with respect to subjecthood for both languages. We also propose an analysis of scrambling based on feature checking (as in (Witkoś 2005)) and show that the possibility of scrambling in a given language depends on the availability of an additional [OCC] feature on the functional heads involved, i.e. T, v or Agr. We show how Polish differs from English in this respect. Finally, we propose a definition of subject based exclusively on feature checking.